2021
DOI: 10.1590/1518-8345.4051.3401
|View full text |Cite
|
Sign up to set email alerts
|

Association between living arrangement and quality of life for older adults in the community

Abstract: Objective: to compare the sociodemographic and economic characteristics of the older adults in the community according to the living arrangement and to verify the association between the type of living arrangement and the quality of life scores. Method: a cross-sectional epidemiological study conducted with 796 older adults in the community. To assess quality of life (dependent variable), network and social support (adjustment variable), validated and applied chi-square tests, descriptive statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
(38 reference statements)
2
12
0
7
Order By: Relevance
“…The present study brings some biosociodemographic relevant information. It stands out, for example, the predominance of male participants (59%), diverging from some national (19)(20)(21)(22) and international (23)(24)(25) studies developed with the elderly. This finding can be justified, in part, by a population-based longitudinal investigation (26) , developed with 1,197 elderly and identified the male gender as a variable associated with the maintenance of internet use over the four years investigated (26) .…”
Section: Discussionmentioning
confidence: 82%
“…The present study brings some biosociodemographic relevant information. It stands out, for example, the predominance of male participants (59%), diverging from some national (19)(20)(21)(22) and international (23)(24)(25) studies developed with the elderly. This finding can be justified, in part, by a population-based longitudinal investigation (26) , developed with 1,197 elderly and identified the male gender as a variable associated with the maintenance of internet use over the four years investigated (26) .…”
Section: Discussionmentioning
confidence: 82%
“…QoL presented a statistical relationship with the type of arrangement: those who lived alone had worse QoL in the physical and psychological domains. In a Brazilian study that used the same instruments, the worst results were found among aged people with this type of arrangement, in the social relationships, death and dying and intimacy domains 11 .…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have also shown the influence of family arrangements on older adults' quality of life, which can either improve or compromise the health and well-being of the oldest members of a family [11][12] . This happens because conflicts, concerns and sadness are present in interpersonal relationships, which tense up with the need for care in old age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is understood that aging is a factor generally associated with a low perception of quality of life, especially in non-developed or developing countries, due to the presence of physical limitations and diseases, especially NCDs ( 25 , 43 45 ). In addition, the type of living arrangement in which the older adults live, usually with sons and/or spouse or alone, favors a low perception of quality of life in this population ( 46 ). On the other hand, adults may be more vulnerable to food insecurity as they are mostly the economically active group of the population that are most subject to unemployment or informal employment.…”
Section: Discussionmentioning
confidence: 99%